Optimization and Evaluation of Soymida Febrifuga Nano Emulsion for Treating Epilepsy - G. Praveen Kumar; V. Suchithra (International Journal of Allied Medical Sciences and Clinical Research, 2024)
Natural plants have always been a very potent source of pharmaceuticals; Indians in particular have been employing a variety of plants, as well as their parts and extracts, for medicinal purposes since the Vedic era. The current study aims to assess the antiepileptic activity of a nanoemulsion made from Soymida febrifuga leaf extract. The Soxhlet device is used to perform the extraction. The ethanol extract was used at dosages of 2000 mg/kg, 1000 mg/kg, 900 mg/kg, 850 mg/kg, 800 mg/kg, and 750 mg/kg for the acute toxicity test. The Soymida febrifuga sample's IR spectra showed that the absorption peaks of different functional groups are consistent with reference spectra. The particle stability index is represented by the zeta potential. The prevention of particle aggregation depends on this stability. The improved formulation's zeta potential was the millivolt (mV) was discovered. The stability of nanoparticles is higher at higher zeta potential maximum. The release study was conducted in accordance with the steps outlined in the section on materials and procedures. The medication was required for the slow, continuous release of the medicine. In the 12-hour release testing, F6, out of the nine formulations, had the highest drug release value. In convulsion models generated by MES and PTZ, the chloroform extract of Soymida febrifuga delayed the onset and decreased the duration of convulsions. It can be utilized as an adjuvant therapy against cognitive deficiency in convulsions.